Preparation method for electrically depositing MnOx material on carbon fiber paper and construction of high-specific-energy supercapacitor
By electrodepositing MnOx material on carbon fiber paper and combining specific electrolytes and cationic membranes to construct ultra-electric devices with wide voltage windows, the problem of supercapacitors being lower than energy is solved, and the effect of high energy density and wide voltage windows is achieved.
Patent Information
- Application Number
- CN202411808833.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The lower specific energy of existing supercapacitors limits their practical application, especially due to the poor conductivity of MnO2 materials and the low voltage window.
By electrodepositing MnOx material on carbon fiber paper, combining two different types of electrolytes, Na2SO4 and NaOH, plus cationic separators, a superelectric device with a wide voltage window is constructed.
The energy density of the MnOx supercapacitor is significantly improved, and the voltage window reaches 1.3-2.6V, which enhances its application potential. Moreover, this method is easy to operate, the raw materials are easy to obtain, and it is non-toxic and harmless.
Smart Images

Figure CN119517631A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical energy storage, and specifically relates to a method for electro-depositing MnO on carbon fiber paper. x Material preparation method and construction of high specific energy supercapacitor. Background Art
[0002] With the rapid development of economy, there is a huge demand for energy consumption. The large consumption of traditional non-renewable mineral energy such as coal, oil and natural gas is accompanied by many environmental problems and sustainable utilization issues. Therefore, finding a large amount of renewable clean energy is crucial to reduce environmental pollution, improve the atmospheric environment, develop a low-carbon economy and promote sustainable development.
[0003] Supercapacitors have a series of advantages such as high specific power, fast charge and discharge rate, long cycle life, and environmental protection. However, compared with traditional batteries, their lower specific energy limits their practical application. If we want to improve the energy density of supercapacitors, we can do so in the following two ways: (1) increase the capacitance of the electrode material to increase the energy density of the device; (2) increase the operating voltage window of the device. According to the energy density formula , by increasing the device voltage window, the energy density of supercapacitors can be increased.
[0004] MnO2 material is cheap, non-toxic and harmless, with a variety of morphological crystal forms. Due to its high theoretical specific capacity (1096 C / g), it is one of the research focuses of supercapacitor electrode materials. However, MnO2 has poor electrical conductivity, so in actual tests, it is far from the theoretical specific capacity of MnO2. From the perspective of improving the conductivity of MnO2, the more common methods are: (1) Compounding with carbon materials, using the large specific surface area and good electrical conductivity of carbon materials to synergize with manganese dioxide, combining the advantages of both, can improve the conductivity of manganese dioxide and improve the electrochemical properties of the composite material; (2) Doping manganese dioxide with corresponding metal ions. Carbon compounding is an important method to improve the performance of manganese dioxide electrode materials, which can improve the conductivity of manganese dioxide and improve its electrochemical properties; (3) Further optimizing the treatment of CFP and MnO by acid washing, KMnO4 oxidation and electrochemical activation. x interface, increasing the MnO x Interface treatment is very important to improve electrochemical performance.
[0005] Due to the limitations of decomposition voltage and the working voltage of electrode materials, the voltage window of super devices is relatively low. Therefore, there are two main methods to improve the voltage window of devices: (1) improving electrode materials and increasing the voltage window of electrode materials; (2) changing the electrolyte used, increasing the electrolyte decomposition voltage and using solid electrolytes, etc. However, these two methods are not very effective in improving the voltage window of devices. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for electrodepositing MnO on carbon fiber paper. x The invention discloses a method for preparing a material and constructing a high specific energy supercapacitor. The invention relates to ... x Electrodeposition of MnO on CFP x This paper provides a new idea. The test results show that the effect of electrodeposition is significant, and its electrochemical performance is significantly improved. Furthermore, starting from the decoupled system electrolyte, the present invention uses two different types of electrolytes, Na2SO4 and NaOH, as positive and negative electrolytes, respectively, and adds a cationic separator to successfully assemble a new type of Mn / / Zn wide voltage window superelectric device, whose voltage window is as high as 1.3-2.6V, which greatly improves the MnO x Energy density of supercapacitors. Only with this special electrolyte system and electrode material system can the high specific energy devices of Mn / / Zn system battery capacitors be assembled.
[0007] The present invention electro-deposits MnO on carbon fiber paper x The method for preparing the material comprises the following steps:
[0008] Step 1: Add CFP to a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, stir at 60-80℃ for 3-8h, rinse repeatedly with ionized water until neutral and dry to increase the hydrophilicity of the material so that it is easier to combine with water molecules and improve the performance of the material.
[0009] Step 2: Add 0.1-20g KMnO4 to 10-100mL ionized water, stir and disperse evenly, then drop 2-10mL 1M HCl solution; add the hydrophilized CFP to the above solution and react for 12h, then wash with ionized water, dry, weigh and test to obtain CFP@MnO x -1, initial growth of MnO on CFP x .
[0010] Step 3: CFP@MnO obtained in step 2 x-1 was treated with electrochemical activation cycle (CD cycle), then washed with 30% H2O2 solution, followed by deionized water washing and drying to make CFP@MnO x -1 The residual manganese-based oxides in the material are removed completely. Interface treatment is very important for improving electrochemical performance.
[0011] Step 4: Place the material obtained in step 3 in an electrodeposition solution for constant current electrodeposition. After the deposition is completed, wash with ionized water and dry to obtain MnO electrodeposited on CFP. x , denoted as CFP@MnO x , and obtain the final electrode material.
[0012] In step 3, the electrolyte used in the electrochemical activation cycle treatment is 0.1M-3M Na2SO4 electrolyte, the CD cycle is ≥5000 times, and the current density is ≥5A / g.
[0013] In step 4, the electrodeposition solution is a mixture of 0.01M-1M Mn(CH3COO)2 and 0.01M-1M Na2SO4, and the constant current electrodeposition time is 50-600S, using 10-400 mA cm -2 Deposition is performed with a current density of 10000 nm. Deposition materials with different loads can be obtained according to different deposition times.
[0014] Further preferably, the electrodeposition solution is a mixture of 0.06M Mn(CH3COO)2 and 0.06M Na2SO4, the constant current electrodeposition time is 300S, and the current is 40 mA cm -2 The deposition area is 1×1cm 2 .
[0015] CFP@MnO prepared by the present invention x Materials to build high specific energy devices.
[0016] Specifically, the CFP@MnO x The material is used as the positive electrode material, Zn foil is used as the negative electrode material, Na2SO4 and NaOH are used as the positive and negative electrolytes respectively, and a cationic separator is added to assemble a new supercapacitor with a wide voltage window. The voltage window can reach 1.3-2.6V, which greatly improves the energy density of supercapacitors, and such devices are easy to carry.
[0017] The beneficial effects of the present invention are embodied in:
[0018] 1. The raw materials used are easy to obtain, non-toxic and harmless, and have low requirements for instruments and equipment and are simple to operate.
[0019] 2. The present invention is based on the strategy of interface modification to electrodeposit MnO on CFP.x Electrode materials significantly improve the specific capacity of the materials and increase their applications in the field of electrochemistry.
[0020] 3. The present invention synthesizes materials with higher specific capacity, expands the device voltage window, and thus greatly improves the energy density of supercapacitors, providing certain possibilities for the practical application and commercial development of supercapacitors in the future.
[0021] 4. The method for constructing a wide voltage window superelectric device of the present invention can be applied in a variety of material systems. The negative electrode uses Zn foil without adjusting the load ratio of different positive and negative electrode materials, and the corresponding appropriate positive and negative electrode electrolytes are selected to realize the construction of a wide voltage window device.
[0022] 5. The method for constructing a novel wide voltage window superelectric device of the present invention uses Na2SO4 as the positive electrode of CFP@MnO x The negative electrode uses NaOH as the electrolyte of Zn foil, and the metal ions in the cation membrane are only Na + Conducting, because the negatively charged groups contained in the cationic membrane used can repel Zn(OH)4 2- Transmembrane transmission prevents Zn dendrites from growing through the membrane, eliminating the performance and safety hazards of Zn dendrites to the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The SEM images of hydrophilic treated CFP at different magnifications, where (a) and (b) are at different magnifications.
[0024] Figure 2 It is CFP@MnO x -1 SEM images of electrode materials at different magnifications. (a) and (b) are at different magnifications.
[0025] Figure 3 CFP@MnO treated with H2O2 x -1. (a) and (b) are SEM images at different magnifications.
[0026] Figure 4 It is CFP@MnO x SEM images of electrode materials at different magnifications. (a) and (b) are at different magnifications.
[0027] Figure 5 It is CFP@MnO x TEM images of electrode materials under transmission electron microscope. (a) and (b) are at different magnifications.
[0028] Figure 6 It is CFP@MnO x EDS image of electrode material under transmission electron microscope.
[0029] Figure 7 It is CFP@MnO x TEM (a) and corresponding SAED image (b) of the electrode material under transmission electron microscopy.
[0030] Figure 8 MnO electrodeposited on CFP x XRD patterns of electrode materials.
[0031] Fig. 9 Electrode material directly grown on CFP using KMnO4, electrochemical performance in a three-electrode system: (a) CV curve; (b) CD curve; (c) specific capacity at different current densities.
[0032] Fig.10 CFP@MnO treated with H2O2 x -1 electrochemical performance in a three-electrode system: (a) CV curve; (b) CD curve; (c) specific capacity at different current densities.
[0033] Fig.11 It is CFP@MnO x Electrochemical performance of electrode materials in the three-electrode system: (a) CV curve; (b) CD curve; (c) specific capacity at different current densities; (d) cycling performance.
[0034] Fig.12 MnO electrodeposited on CFP x Electrochemical performance of electrode materials in different windows in the three-electrode system: (a) Comparison of CD curves at a current density of 1 A / g; (b) Comparison of specific capacities at different current densities.
[0035] Fig.13 MnO electrodeposited on CFP x High loading of electrode materials: (a) CV curve; (b) CD curve; (c) specific capacitance at different current densities.
[0036] Fig.14 Electrochemical performance of the assembled double-groove wide voltage window device: (a) CV curve; (b) CD curve; (c) specific capacitance at different current densities; (d) cycling performance; (e) Ragone plot.
[0037] Fig.15 Assembled wide voltage window glue-mounted soft package device: (a) display of the complete device; (b) about the positive electrode CFP@MnO x(c) side display of the soft-package device; (d) display of the negative electrode Zn foli.
[0038] Fig.16 Electrochemical performance of the assembled soft-package wide voltage window device: (a) CV curve; (b) CD curve; (c) specific capacitance at different current densities.
[0039] Fig.17 Direct electrodeposition of MnO using CFP x Composite materials: (a) CV curve; (b) CD curve; (c) specific capacitance at different current densities. DETAILED DESCRIPTION
[0040] The following embodiments related to the present invention are specifically described by way of examples, which are only limited examples used to illustrate the embodiments of the present invention and do not limit the scope of the present invention.
[0041] Embodiment 1:
[0042] 1. Electrodeposition of MnO on CFP x Electrode Materials
[0043] First, the CFP was hydrophilized, and after weighing the hydrophilized CFP, 0.4 g KMnO4, 40 mL ionized water, and 2 mL 1 M HCl were added to react, stirred at 60 ° C for two hours on a heating table, and continued to react at room temperature for 12 hours, and then washed with ionized water, dried, weighed, and tested to obtain CFP@MnO x -1; the samples were electrochemically activated (CD cycles ≥ 5000 times, current density ≥ 5A / g, window -0.1-1.1V), then cleaned with 30% H2O2, followed by ionized water washing, oven drying, weighing the CFP weight, and then testing and constant current electrodeposition (40 mA cm -2 The deposition was carried out at a current density of 1.000 Å, the electrolyte was 0.06 M Mn(CHCOO)2 and 0.06 M Na2SO4), and the deposition area was 1 × 1 cm 2 After the deposition, the product was washed with ionized water, dried, and weighed to obtain CFP@MnO x .
[0044] The present invention first uses MnO x The MnO x After peeling and cleaning, further electrodeposition was performed to finally obtain CFP@MnO x Electrode material, namely CFP@MnO x . Interface treatment is very important for improving electrochemical performance.
[0045] 2. Preparation of Na2SO4 and NaOH electrolyte
[0046] Prepare 1M Na2SO4 by dissolving 14.2 g Na2SO4 in 100 mL ionized water under stirring. Stir at room temperature for 2 h until the solution becomes clear.
[0047] Prepare 1M NaOH by dissolving 4 g of NaOH in 100 mL of ionized water under stirring. Stir at room temperature for 2 h until the solution becomes clear.
[0048] 3. Construction of wide voltage window superelectric devices
[0049] (1) Assemble a three-electrode system and electrodeposit 1×1 cm MnO on CFP x The active material is 0.06M Mn(CH3COO)2 and Na2SO4. The mass before and after electrodeposition is weighed and the load is calculated. After washing with ionized water and drying, it is used as the working electrode. 1 M Na2SO4 solution is used as the electrolyte, Ag / AgCl is the reference electrode, and Pt sheet is the counter electrode CFP@MnO x The electrode material is a working electrode, and the electrochemical performance of the electrode material in a three-electrode system is tested;
[0050] (2) Assemble into devices, electrodeposit MnO on CFP x Electrode material, Zn foil as negative electrode material, prepare positive and negative electrodes according to the three-electrode system steps. Place Na2SO4 and NaOH electrolytes in the positive and negative electrolyte tanks respectively, separated by a cationic membrane in the middle, and obtain a wide voltage window super-water system device.
[0051] The following conclusions can be drawn from the attached figure:
[0052] Figure 1 The SEM image in the figure reveals the rod-like morphology of CFP. At high magnification, it can be seen that it has a relatively large specific surface area, which can provide corresponding attachment sites.
[0053] Figure 2 The SEM image in the figure shows the morphology of MnO2 grown on CFP due to the strong oxidizing property of KMnO4 and the reducing property of carbon. It appears as round particles under high magnification.
[0054] Figure 3 CFP@MnO treated with H2O2 x -1 SEM, the attachments have no round particles, and there are corresponding attachment points under high magnification.
[0055] Figure 4 SEM image of the final synthesized CFP@MnOx The overall structure is flake-like.
[0056] Figure 5 The TEM image in the middle further verifies the CFP@MnO x In the scanned image, the active material is attached to the substrate.
[0057] Figure 6 CFP@MnO x Energy spectrum of electrode materials. The figure clearly shows the uniform distribution of the three elements C, Mn, and O, proving that MnO was successfully electrodeposited. x .
[0058] Figure 7 It is CFP@MnO x TEM and corresponding SAED images of the electrode material under transmission electron microscope.
[0059] Figure 8 CFP@MnO x The XRD patterns of the electrode materials show that Mn3O4, MnO2 (MnO x )These two manganese-based oxides.
[0060] Fig. 9 It is an electrode material grown directly by CFP using KMnO4. The electrochemical performance test in the three-electrode system is Fig. 9 (a) The CV curve shows that the response of current to voltage is approximately symmetrical, indicating that the material has a reversible reaction; Fig. 9 (b) The CD curve is approximately an isosceles triangle, indicating that the material has good conductivity; Fig. 9 (c) is the specific capacity at different current densities. At 1 A / g, the specific capacitance of the material is 134.2 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 134.2, 120.4, 99, 80, and 64 F / g, respectively, which are relatively low.
[0061] Fig.10 CFP@MnO after cleaning with H2O2 x -1 Electrochemical performance in three-electrode system: Fig.10 (a) There is no obvious polarization phenomenon in the CV curve; Fig.10 (b) The CD curve does not resemble an isosceles triangle and has a relatively low Coulomb efficiency; Fig.10 (c) Specific capacity at different current densities, 1 mA / cm 2 When the material has a specific capacitance of 46.4 F / cm 2 , at current densities of 1, 2, 5, and 10 mA / cm2 When the specific capacities of the electrodes are 46.4, 32.2, 23, and 18 F / cm 2 , indicating that the capacity is very low.
[0062] Fig.11 CFP@MnO x Electrode material testing in a three-electrode system. Fig.11 (a) The CV curve shows that there is no obvious polarization phenomenon, indicating that the material has excellent supercapacitor properties and highly reversible reaction. Fig.11 (b) The CD curve of the sample is approximately an isosceles triangle, and there is no obvious voltage drop, indicating that the electrode material has good conductivity and good capacitive behavior. Fig.11 (c) The specific capacity of the electrode material calculated from the CD curve shows that at a current density of 1 A / g, the material specific capacitance is as high as 760.5 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 760.5, 680.4, 596.5, 539, and 442 F / g, respectively. At a current density of 5 A / g, the capacity retention rate is 100%, indicating relatively good rate performance. The CFP@MnO obtained in this embodiment x The capacity of the electrode material remained almost unchanged after 3000 cycles of charge and discharge at a constant current of 5A / g, indicating that the electrode material has excellent cycle stability.
[0063] Fig.12 CFP@MnO x The electrochemical properties of the electrode material in different windows in the three-electrode system are as follows: at 1A / g, the specific capacity of the electrode in the -0.1-0.9V window is 760.5 C / g, the specific capacity of the electrode in the -0.1-1.0V window is 836.8C / g, and the specific capacity of the electrode in the -0.1-1.1V window is 896.6C / g.
[0064] Fig.13 CFP@MnO x The electrochemical performance of the electrode material with high loading in different windows in the three-electrode system is as follows: at a current density of 0.5 A / g, the specific capacity of the electrode in the -0.1-0.9 V window is 407.8 F / g; at current densities of 1, 2, 5 and 10 A / g, the specific capacity of the electrode is 387, 349, 283.5 and 200 F / g, respectively.
[0065] Fig.14 Electrochemical performance of superelectric devices with wide voltage windows, Fig.14(a), (b) CV, CD curves show that when the voltage window is 2.6V, there is still no obvious side reaction, which is relatively stable. Calculated from the CD curve, when the current density is 0.5A / g, the device specific capacity is as high as 568.99 F / g, that is, at a power density of 975 W / kg, the energy density is 400.67Wh / kg, which greatly improves the MnO x Energy density of superelectric devices. Fig.14 (e) Ragone plot. The device achieves a maximum specific energy of 400.67 Wh / kg at a power density of 975 W / kg, showing superior performance compared to other superelectric devices. Therefore, the new wide-voltage superelectric device we constructed has greater advantages over superelectric devices.
[0066] Fig.15 This is a display diagram of a new wide voltage window superelectric device in a soft-pack packaging. The positive and negative electrodes are encapsulated separately and separated by a cationic membrane. Fig.15 (a) is a schematic diagram of the entire device; Fig.15 (b), (c), and (d) show the positive pole, side pole, and negative pole in all directions.
[0067] Fig.16 Electrochemical performance of soft-packaged wide voltage window superelectric devices, Fig.16 (a), (b) CV, CD curves show that no obvious side reactions occur when the voltage window is 2.6 V. Calculated from the CD curve, at a current density of 1 A / g, the device specific capacity reaches 188.45 F / g, that is, at a power density of 1950 W / kg, the energy density is 132.7 Wh / kg. However, as can be seen from the figure, the device has a large voltage drop, which may be related to the large resistance of the cationic membrane we use. Later, we will start from reducing the resistance and improve the device.
[0068] Fig.17 Direct electrodeposition of MnO for CFP x Electrochemical properties of electrode materials at different windows in the three-electrode system, Fig.17 (a) There is no obvious polarization phenomenon in the CV curve, indicating that the material has a highly reversible reaction. Fig.17 (b) The CD curve of the sample is approximately an isosceles triangle, and there is no obvious voltage drop, which means that the electrode material has good conductivity and good capacitive behavior. Fig.17 (c) The specific capacity of the electrode material calculated based on the CD curve shows that at a current density of 1 A / g, the material specific capacitance reaches 301 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 301, 272, 239.5, 211, and 175.8 F / g, respectively.
[0069] Embodiment 2:
[0070] 1. Electrodeposition of MnO on CFP x Electrode Materials
[0071] CFP@MnO x The preparation of electrode materials is shown in Example 1.
[0072] 2. The electrolyte configuration of Na2SO4 and NaOH is the same as that in Example 1.
[0073] 3. Construction of wide voltage window superelectric devices
[0074] The obtained CFP@MnO x Electrode Materials Electrodes were prepared according to the steps in Example 1, and their performance was tested under a three-electrode system. Fig.14 (a) The CV curve shows that the redox peak is obvious and the polarization phenomenon is not obvious. Fig.14 (b) The CD curve of the sample has an obvious voltage drop, indicating that the resistance is relatively large, which is related to the ion transport capacity of the cationic membrane. Fig.14 (c) The specific capacity of the aqueous superelectric device calculated from the CD curve is calculated based on the positive electrode material. At a current density of 0.5A / g, the device specific capacitance is as high as 568.9F / g, showing a high capacity. At 1, 2, and 5A / g, the specific capacities of the device are 448.84, 305.07, and 118.07 F / g, respectively. At a current density of 5A / g, the capacity retention rate after 7000 cycles is 83.1%, indicating relatively good cycle stability. 1M Na2SO4 is used as the positive electrode of CFP@MnO x The negative electrode uses 1M NaOH as the electrolyte of Zn foil. The cationic membrane only allows cations to pass through, so the metal ions are only Na + Conducting, because the negatively charged groups contained in the cationic membrane used can repel Zn(OH)4 2- Transmembrane transmission prevents Zn dendrites from growing through the membrane, eliminating the performance and safety hazards of Zn dendrites to the device.
[0075] Embodiment 3:
[0076] 1. CFP@MnO x Preparation of electrode materials
[0077] CFP@MnO x The preparation of electrode materials is shown in Example 1.
[0078] 2. Preparation of Na2SO4 and NaOH electrolyte
[0079] The preparation of Na2SO4 and NaOH electrolytes is shown in Example 1.
[0080] Fig.11 Electrodeposition of 100S on CFP to load 1.3mg-MnO x In the three-electrode system test, Fig.11 (a) The CV curve shows that there is no obvious polarization phenomenon, indicating that the material has excellent supercapacitor properties and highly reversible reaction. Fig.11 (b) The CD curve of the sample is approximately an isosceles triangle, and there is no obvious voltage drop, indicating that the electrode material has good conductivity and good capacitive behavior. Fig.11 (c) The specific capacity of the electrode material calculated from the CD curve shows that at a current density of 1 A / g, the material specific capacitance is as high as 760.5 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 760.5, 680.4, 596.5, 539, and 442 F / g, respectively, which shows a relatively high capacity.
[0081] Fig.13 Electrodeposition of 300S high loading 3.2mg-MnO on CFP x Electrode material testing in a three-electrode system. Fig.13 (a) The CV curve shows no obvious polarization phenomenon, indicating that the material has excellent supercapacitor properties and highly reversible reactions. Fig.13 (b) The CD curve of the sample is approximately an isosceles triangle and does not show an obvious voltage drop, indicating that the electrode material has good conductivity. Fig.13 (c) The specific capacity of the electrode material calculated from the CD curve shows that at a current density of 0.5 A / g, the material specific capacitance is as high as 407.8 F / g. At current densities of 0.5, 1, 2, 5, and 10 A / g, the specific capacities of the electrode are 407.8, 387, 349, 283.5, and 200 F / g, respectively, indicating relatively good rate performance.
[0082] Embodiment 4:
[0083] 1. CFP@MnO x Preparation of electrode materials
[0084] CFP@MnO x The preparation of electrode materials is shown in Example 1.
[0085] 2. Preparation of Na2SO4 and NaOH electrolyte
[0086] The preparation of Na2SO4 and NaOH electrolytes is shown in Example 1.
[0087] 3. Construction of assembling glue-bonded wide voltage window superelectric devices
[0088] The positive electrode was prepared according to the preparation method of the three-electrode system. x The material is used as the positive electrode and Zn as the negative electrode to assemble the soft-package device; the positive electrode electrolyte is 1M Na2SO4 and the negative electrode electrolyte is 1M NaOH, separated by a cationic membrane in the middle, and the voltage window can reach 1.3-2.6V, which improves the energy density of the supercapacitor, and such devices are easy to carry and assemble. At a current density of 1A / g, the device has a specific capacity of 188.45F / g, that is, at a power density of 1950W / kg, the energy density is 132.7Wh / kg, Fig.15 (a) We can see that this is the overall display of the glue-mounted soft package device, and the positive and negative electrodes are connected for testing. Fig.16 (a) CV curve (b) CD curve. It can be seen from the figure that when the current density is 1A / g, there is a voltage drop of about 0.4V. At this time, the resistance is large. At this time, the device specific capacity reaches 188.45F / g, that is, at a power density of 1950W / kg, the energy density is 132.7Wh / kg. At a current density of 2A / g, the device specific capacity reaches 132.99F / g, that is, at a power density of 974.92W / kg, the energy density is 93.64Wh / kg. At a current density of 5A / g, the device specific capacity reaches 31.54F / g, that is, at a power density of 389.97W / kg, the energy density is 43.33Wh / kg. Compared with the double-slot width voltage water system device, the specific energy has dropped significantly. We speculate that the reason for the drop is related to the size of the resistance.
[0089] Embodiment 5:
[0090] 1. CFP@MnO x Preparation of electrode materials
[0091] CFP@MnO x The preparation of electrode materials is shown in Example 1.
[0092] 2. Preparation of Na2SO4 and NaOH electrolyte
[0093] The preparation of Na2SO4 and NaOH electrolytes is shown in Example 1.
[0094] 3. CFP and MnO prepared by different methods x Comparison of composite material properties.
[0095] Fig. 9 It is an electrode material grown directly by CFP using KMnO4. The electrochemical performance test in the three-electrode system is Fig. 9 (a) The CV curve shows that the response of current to voltage is approximately symmetrical, indicating that the material has a reversible reaction; Fig. 9(b) The CD curve is approximately an isosceles triangle, indicating that the material has good conductivity; Fig. 9 (c) is the specific capacity at different current densities. At 1 A / g, the specific capacitance of the material is 134.2 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 134.2, 120.4, 99, 80, and 64 F / g, respectively, which are relatively low.
[0096] Fig.17 Direct electrodeposition of MnO for CFP x Electrochemical properties of electrode materials at different windows in the three-electrode system, Fig.17 (a) The obvious polarization phenomenon in the CV curve indicates that the material has a highly reversible reaction. Fig.17 (b) The CD curve of the sample is approximately an isosceles triangle, and there is no obvious voltage drop, indicating that the electrode material has good conductivity and good capacitive behavior. Fig.17 (c) The specific capacity of the electrode material calculated from the CD curve shows that at a current density of 1 A / g, the material specific capacitance is as high as 301 F / g. At current densities of 1, 2, 5, 10 and 20 A / g, the specific capacities of the electrode are 301, 272, 239.5, 211, and 175.8 F / g, respectively. The material has good rate performance.
[0097] Fig.11 CFP@MnO x In the three-electrode system test, Fig.11 (a) The CV curve shows that there is no obvious polarization phenomenon, indicating that the material has excellent supercapacitor properties and highly reversible reaction. Fig.11 (b) The CD curve of the sample is approximately an isosceles triangle, and there is no obvious voltage drop, indicating that the electrode material has good conductivity and good capacitive behavior. Fig.11 (c) The specific capacity of the electrode material calculated from the CD curve shows that at a current density of 1 A / g, the material specific capacitance is as high as 760.5 F / g. At current densities of 1, 2, 5, 10, and 20 A / g, the specific capacities of the electrode are 760.5, 680.4, 596.5, 539, and 442 F / g, respectively, which shows a relatively high capacity.
Claims
1. Electrodeposition of MnO on carbon fiber paper x The method for preparing the material is characterized in that The steps include: Step 1: Add CFP to a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, stir at 60-80°C for 3-8h, rinse repeatedly with deionized water until neutral and dry; Step 2: Add 0.1-20g KMnO4 into 10-100mL ionized water, stir and disperse evenly, then drop 2-10mL 1M HCl solution; add the hydrophilized CFP into the above solution and react for 12h, then wash with ionized water and dry to obtain CFP@MnO x -1; Step 3: CFP@MnO obtained in step 2 x -1 was subjected to electrochemical activation cycle treatment, followed by cleaning with 30% H2O2 solution, followed by ionized water washing and drying; Step 4: Place the material obtained in step 3 in an electrodeposition solution for constant current electrodeposition. After the deposition is completed, wash with ionized water and dry to obtain CFP@MnO x Material.
2. The preparation method according to claim 1, characterized in that: In step 3, the electrolyte used in the electrochemical activation cycle treatment is a 0.1M-3M Na2SO4 solution.
3. The preparation method according to claim 2, characterized in that: In step 3, during the electrochemical activation cycle treatment, the number of cycles is ≥5000 times and the current density is ≥5A / g.
4. The preparation method according to claim 1, characterized in that: In step 4, the electrodeposition solution is a mixture of 0.01M-1M Mn(CH3COO)2 and 0.01M-1M Na2SO4.
5. The preparation method according to claim 4, characterized in that: In step 4, the electrodeposition solution is a mixture of 0.06M Mn(CH3COO)2 and 0.06M Na2SO4.
6. The preparation method according to claim 4, characterized in that: In step 4, the constant current electrodeposition time is 50-600S, and the current is 10-400 mA / cm 2 The deposition was carried out at a current density of .
7. The preparation method according to claim 6, characterized in that: In step 4, the constant current electrodeposition time is 300 s, and the current is 40 mA / cm 2 The deposition was carried out at a current density of .
8. CFP@MnO prepared according to any one of the preparation methods in claims 1-7 x Application of materials in the construction of high specific energy supercapacitors.
9. The use according to claim 8, characterized in that: The CFP@MnO x The material is used as the positive electrode material, Zn foil is used as the negative electrode material, Na2SO4 and NaOH are used as positive and negative electrolytes respectively, and a cationic separator is added to assemble a new superelectric device with a wide voltage window.
Citation Information
Patent Citations
Preparation method of MnO2 / carbon fiber composite electrode and capacitor with MnO2 / carbon fiber composite electrode
CN111933456A
Preparation of manganese-based high-voltage window electrode material and supercapacitor energy storage device
CN114974931A
MnO2 flexible supercapacitor electrode material and preparation method thereof
CN115020113A
Activation method of high-load manganese dioxide electrode material
CN117800398A
Energy Storage from Cellulose Fiber Materials
US20130279075A1